A note on market competition, advanced manufacturing technology and management accounting and control systems change / Che Ruhana Isa - Isa, Che Ruhana (Accounting Research Institute (ARI) & Faculty of Accountancy, 2007)
Changes in competitive and manufacturing environments have important implications for designing appropriate management accounting and control systems (MACS) in organizations. This paper examines the effect of market competition and advanced manufacturing technology on management accounting and control systems change. Using a sample of 110 Malaysian manufacturing firms, this study investigated the roles of perceived market competition, advanced manufacturing technology adoption and employee attitude toward change in predicting MACS change. Hypotheses were tested using both quantitative and qualitative data collected by a questionnaire survey and post-survey interviews. It was hypothesized that changes in perceived market competition and changes in advanced manufacturing technology adoption directly affect changes in MACS.